(untitled) (Journal of Academic Research, 2023)
The basic function of human language is communication between people, through various systems, including speech and writing, in which clarity and explanation are required. However, you may find within the linguistic system some ambiguity, concealment and multiplicity of meanings, due to semantic relationships, grammatical structure, or the complexity of its construction. Or because of correction and distortion in the written language, or because of ambiguity in the artistic image, or because of ambiguity in the context that makes it bear more than one meaning. This research reviews the definition of the phenomenon of ambiguity, the position of linguists, grammarians, and rhetoricians and their efforts in studying this phenomenon, then mentions some examples of terms indicating ambiguity, and clarifies their lexical and semantic meaning.